Mapeamento de solos atraves de imagens de radar e de satelite. - Garcia, G. J.; Marchetti, D. A B; Espindola, C. R. (My University, 1985)
The objective of the present work was the improvement of the methodology for soil mapping through the drainage network with the aid of Landsat data. The drainage network of the area studied was delineated and the soils identified. The main problem of the method has been the characterization of the contact between soil units when it is not abrupt, and in this case field trips and the analysis of the relief has been used to solve doubts.-from English summary
Soil mapping through radar and Landsat images